2010
DOI: 10.4188/jte.56.71
|View full text |Cite
|
Sign up to set email alerts
|

Papermaking from Waste Silk and Its Application as Reinforcement of Green Composite

Abstract: In order to recycle the waste silk resource effectively, the biodegradable composite consisting of PBS matrix and pure silk paper was prepared by hot compression molding. Beating treatment was adopted to modify silk fibroin and enhance the composite, and the corresponding mechanical properties and morphologies were studied in detail. The results showed that beating treatment could realize the fibrillation of fibroin and improve the tensile strength of silk paper, and proper beating treatment to fibroin could a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“…Their mechanical properties greatly depend on the interaction between the binder and fibers. To improve the interaction between the binder and fiber, chemical modifications (Dányádi et al, 2010;Guo et al, 2016;Lee et al, 2019) (i.e., ionic, electrostatic, polar, and van der Waals forces exerted on the fiber and adhesive) and physical modifications of the fiber surfaces (Song et al, 2010), which increase the roughness and specific surface area of the fibers, have been widely used (Adekunle, 2015). However, these modifications lead to the physicochemical damage of the fibers and thus the mechanical weakness of the product if the modification time is extensive (Baiardo et al, 2004;Carvalho et al, 2010;Favaro et al, 2010;Das et al, 2015;Pandey et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Their mechanical properties greatly depend on the interaction between the binder and fibers. To improve the interaction between the binder and fiber, chemical modifications (Dányádi et al, 2010;Guo et al, 2016;Lee et al, 2019) (i.e., ionic, electrostatic, polar, and van der Waals forces exerted on the fiber and adhesive) and physical modifications of the fiber surfaces (Song et al, 2010), which increase the roughness and specific surface area of the fibers, have been widely used (Adekunle, 2015). However, these modifications lead to the physicochemical damage of the fibers and thus the mechanical weakness of the product if the modification time is extensive (Baiardo et al, 2004;Carvalho et al, 2010;Favaro et al, 2010;Das et al, 2015;Pandey et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The flexural properties of silk/bamboo hybrid paper reinforced PBS green composite and PBS control were measured using a three-point bending method according to JIS K7171, the specimen dimension was 60 × 15 × 3 mm 3 , and the span-to-depth ratio was 16. A cross head speed of 5 mm/min was used.…”
Section: Flexural Propertiesmentioning
confidence: 99%
“…Silk fibroin is featured with hierarchical structure. Former studies [15,16] indicated that beating treatment to fibroin can realize fibrillation, and add the specific surface area of fibers and the combining the energy between fibers, which are 1 * Corresponding author : E-mail : sry__2002@hotmail.com, Tel/Fax : +81-75-724-7863…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of these properties, processes and applications utilizing natural fibers as reinforcement for plastic composites have been increasingly studied by many researchers in recent years [3][4][5]. In previous studies by our research group [6,7], both silk paper-and silk/ bamboo paper-reinforced poly(butylene succinate) (PBS) green composites have been developed using waste silk, and the corresponding mechanical properties have been studied in detail. Papermaking results in a network structure containing an improved distribution of short fibers, aiding connectivity between the fibers.…”
Section: Introductionmentioning
confidence: 99%